Beyond Brain Drain: The Dynamics of Geographic Mobility and Educational Attainment of B.C. Young Women and Men - Andres, Lesley; Licker, Aaron (Canadian Journal of Higher Education, 2005)
In recent years, the topic of "brain drain" has gained considerable attention, both in public and intellectual spheres. Despite the media frenzy, few data sets and related studies exist to examine the nature and extent to which brain drain occurs. The purpose of this study is to extend the scope of the way we think about "brain drain," both conceptually and analytically, by examining the geographic migration and mobility patterns over a 10 year period of a large sample of young adults from British Columbia. Through analyses of detailed longitudinal questionnaire data, we examine geographic mobility patterns in relation to (a) B.C. college region of origin, (b) post-secondary educational completion patterns, and (c) gender. Findings reveal that migration patterns are both gendered and geographically complex. Our findings support the claim that brain drain to the U.S. is a mere trickle, not a flood. When examining gender differences of respondents living in the U.S. and outside North America, the vast majority of women who live outside of Canada have earned university credentials, which suggests that global mobility for women appears to be related to university degree completion. These findings challenge the narrow definition of brain drain as simply a Canada - U.S.A. issue where Canada's "best and brightest" are lured from Canada and invite us to consider the implications of intra- and extra-provincial brain drain (and gain), primarily within the confines of Canada.